Analysis of the Relationship between Dockless Bicycle-Sharing and the Metro: Connection, Competition, and Complementation - Yuru Wu; Weifeng Li; Qing Yu; Jian Li (Journal of Advanced Transportation)
Dockless bicycle-sharing (DLBS) is one of the novel transportation modes emerging in recent years. As a newly arisen mode, dockless bicycle-sharing inevitably has influence on the existing components of the public transportation system, especially the metro system. A large number of scholars have explored the integration relationship between the two. However, through the evaluation and quantification of the dockless bicycle-sharing data and the metro automatic fare collection data, we find that the relationship between the two is not unique. Based on the location of origin and destination, the travel duration, and the travel distance, the dockless bicycle-sharing trips closely related to the metro were identified and categorized into three different temporal-spatial relationships: competition trips, connection trips, and complementation trips. Three indicators were proposed to characterize the relationship between the two systems. A case study was carried out in Shanghai, China. The proposed method was applied to investigate when, where, and to what extent the dockless bicycle-sharing trips compete with, integrate with, and complement the metro. The results show that dockless bicycle-sharing mainly integrates with and complements the metro. It is where the dockless bicycle-sharing trip takes place and the trip significantly determines its relationship with the metro. The findings provide significant implications regarding the design and management of dockless bicycle-sharing and the metro.